Correlation study between apparent diffusion coefficients and the prognostic factors in breast cancer. Issue 5 (May 2023) - Dai, X.; Shen, Y.; Gao, Y.; Huang, G.; Lin, B.; Liu, Y.
Abstract : Aim: To analyse the correlation between apparent diffusion coefficients (ADC) derived from intratumoural and peritumoural regions with prognostic factors and immune–inflammatory markers in breast cancer (BC). Materials and methods: In this retrospective study, 89 patients (age range, 28–66 years; median, 45 years) with a diagnosis of invasive BC who underwent routine blood tests and multiparametric magnetic resonance imaging (MRI) were enrolled. The study cohort was stratified according to tumour maximum cross-section ≥20 mm, lymph node metastasis (LNM), time–signal intensity curve (TIC) type, and receptor status. Minimum, maximum, mean, and heterogeneity values of tumour ADC (ADCtmin, ADCtmax, ADCtmean, and ADCheter ), maximum values of peritumoural ADC (ADCpmax ), and the ratio of peritumoural–tumour ADC (ADCratio ) were obtained on the ADC maps. Linear regression analyses were performed to investigate the correlation between immune–inflammatory markers, prognostic factors and ADC values. Results: HER-2 was positively associated with ADCtmax, ADCtmean, and ADCpmax values ( β = 0.306, p =0.004; β = 0.283, p =0.007; β = 0.262, p =0.007, respectively), while platelet-to-lymphocyte ratio (PLR) was positively associated with ADCpmax and ADCratio values ( β = 0.227, p =0.020; β = 0.231, p= 0.020, respectively). Among ADC parameters, ADCpmax showed the highest predictive values for evaluating the presence of LNM (AUC, 0.751; sensitivity, 70.4%; specificity, 77.1%). Conclusion: The ADCpmax value could provide additional assistance in predicting prognostic factors of BC. Highlights: HER-2 and platelet-to-lymphocyte ratio were associated with peritumoral ADC value. ADC had good predictive values for evaluating the presence of lymph node metastasis. Peritumoral ADC had higher diagnostic values than intratumoral ADC in breast cancer.